Bio-based binder, electrode paste and preparation method of bio-based binder and electrode paste

By using bio-based binders prepared from alcohol, plant asphalt, syrup and starch, combined with aggregate and concave and concave and concave and concave and concave and concave and concave soil, the problems of harmful substance release and poor mechanical strength in the existing electrode paste binders are solved, and the electrode paste with high mechanical strength and low porosity is achieved, meeting environmental protection and performance requirements.

CN119570443AActive Publication Date: 2025-03-07AIKEN CARBON (CHINA) CO LTD

Patent Information

Application Number
CN202411620008.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-07
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

There are harmful organic molecules in the binder of the existing electrode paste, which will release toxic and harmful gases during roasting, affecting the environment and health. At the same time, the mixing of plant asphalt, syrup and gelatinized starch as electrode paste binder has problems of poor mechanical strength and high porosity.

Method used

A bio-based binder with alcohol, plant asphalt, syrup, starch with a purity of 55% to 65%, was prepared by specific stirring steps and temperature control, and mixed with aggregate and concave and concave bar soil for molding to form an electrode paste with high mechanical strength and low porosity after calcination.

Benefits of technology

The mechanical strength of the electrode paste is improved and the porosity reduction is reduced, and the release of toxic gases during roasting is avoided, and environmental protection and performance requirements are met.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode paste. The invention provides a bio-based binder. The invention also provides a preparation method of the bio-based binder. The invention also provides an electrode paste based on the bio-based binder. The electrode paste comprises 80-90 parts by mass of aggregate, 10-20 parts by mass of the bio-based binder and 0.7-1.2 parts by mass of attapulgite, wherein the bio-based binder comprises alcohol with the purity of 55%-65%, vegetable pitch, syrup and starch, and the mass ratio of the alcohol to the vegetable pitch to the syrup to the starch is (20-25): (150-170): (70-85): (90-110). The invention further provides a preparation method of the electrode paste based on the bio-based binder, the prepared binder is environmentally friendly and good in uniformity, and meanwhile the cold ramming paste prepared according to the preparation method of the cold ramming paste is high in mechanical strength and low in porosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode paste, and in particular relates to a bio-based binder and an electrode paste and a preparation method thereof. Background Art

[0002] Cold rammed paste is an electrode paste that can be used for masonry construction at room temperature. It is widely used in industrial furnaces such as aluminum electrolytic cells, ironmaking blast furnaces, smelting furnaces, and calcium carbide furnaces. At present, the binders of cold rammed paste are mainly asphalt, tar, and anthracene oil. These binders are mainly extracted from natural minerals, such as petroleum, coal, etc. Although these binders have been chemically purified, the harmful organic molecules in them are still difficult to completely remove. For example, polycyclic aromatic hydrocarbons (PAH) exist in asphalt, and PAH is highly carcinogenic. The electrode paste made of these binders will release a large amount of toxic and harmful gases during the mixing and kneading molding and subsequent high-temperature roasting stages, which will harm the environment and people's health.

[0003] At present, plant asphalt, syrup, gelatinized starch, etc. can be used as binders for electrode paste, but there are certain technical obstacles to mixing the three as binders for electrode paste. First of all, the fluidity of plant asphalt is poor, and it needs to be kneaded at a higher temperature, and the uniformity of the electrode paste after kneading is poor. Gelatinized starch is a solid powder, and plant asphalt and syrup as binders themselves have greater viscosity. When the three are mixed together, a single component is easy to clump, resulting in uneven distribution of the three components of the binder. The viscosity of starch, including gelatinized starch, is low. After the binder is added to starch, it is easy to cause poor mechanical strength of the electrode paste in the case of uneven mixing, which cannot meet the use requirements. Secondly, although all three are viscous, the viscosity difference is large, and the viscosity is also related to temperature. The proportion and temperature of the three ultimately affect the uniformity and compactness of the electrode paste during kneading. If the compactness of the mixed and kneaded electrode paste is not enough, then after subsequent high-temperature roasting, the mechanical strength of the obtained electrode paste is low. Summary of the invention

[0004] Based on this, it is necessary to provide an environmentally friendly and healthy bio-based binder.

[0005] There is also a need to provide an electrode paste based on a bio-based binder, which has high mechanical hardness and low porosity after calcination.

[0006] It is also necessary to provide a method for preparing an electrode paste based on a bio-based binder, wherein the prepared electrode paste has high mechanical hardness and low porosity after calcination.

[0007] A bio-based binder includes alcohol with a purity of 55% to 65%, plant asphalt, syrup and starch, and the mass ratio of the alcohol, plant asphalt, syrup and starch is (20 to 25): (150 to 170): (70 to 85): (90 to 110).

[0008] A method for preparing a bio-based binder comprises the following steps:

[0009] Step 1: Add 55% to 65% purity alcohol, vegetable asphalt, syrup, and starch into a stirring container, and mix them in a mass ratio of (20 to 25): (150 to 170): (70 to 85): (90 to 110);

[0010] Step 2: Stir the alcohol and starch at a speed of 40-60 r / min for 2-3 min at an ambient temperature of 20-30 degrees Celsius;

[0011] Step 3: Continue to add syrup and stir at a speed of 80-100 r / min for 5-8 min at an ambient temperature of 40-50 degrees Celsius;

[0012] Step 4: Continue to add plant asphalt and stir at a speed of 40 to 70 r / min for 10 to 15 minutes at an ambient temperature of 50 to 55 degrees Celsius to obtain a bio-based binder.

[0013] An electrode paste based on a bio-based binder includes 80 to 90 parts by mass of aggregate, 10 to 20 parts by mass of a bio-based binder, and 0.7 to 1.2 parts by mass of attapulgite, wherein the bio-based binder includes alcohol, plant asphalt, syrup, and starch with a purity of 55% to 65%, and the mass ratio of the alcohol, plant asphalt, syrup, and starch is (20 to 25): (150 to 170): (70 to 85): (90 to 110).

[0014] A method for preparing an electrode paste based on a bio-based binder comprises the following steps:

[0015] Step 1: Add 55% to 65% purity alcohol, vegetable asphalt, syrup, and starch into a stirring container, and mix them in a mass ratio of (20 to 25): (150 to 170): (70 to 85): (90 to 110);

[0016] Step 2: Stir the alcohol and starch at a speed of 40-60 r / min for 2-3 min at an ambient temperature of 20-30 degrees Celsius;

[0017] Step 3: Continue to add syrup and stir at a speed of 80-100 r / min for 5-8 min at an ambient temperature of 40-50 degrees Celsius;

[0018] Step 4: Continue to add plant asphalt and stir at a speed of 40 to 70 r / min for 10 to 15 minutes at an ambient temperature of 50 to 55 degrees Celsius to obtain a bio-based binder;

[0019] Step 5: Mix the bio-based binder, aggregate and attapulgite and knead them into shape, wherein the mass ratio of the aggregate, the bio-based binder and the attapulgite is (80-90):(10-20):(0.7-1.2), the kneading temperature is 55-75 degrees Celsius, and the time is 50-60 minutes.

[0020] Beneficial effects: The bio-based binder of the present invention is completely composed of plant components and does not produce toxic and harmful gases at high temperatures. At the same time, the present invention utilizes the physical and chemical properties of different components of the binder to prepare a binder with uniform components, and the prepared environmentally friendly binder has good uniformity. At the same time, the electrode paste prepared according to the preparation method of the electrode paste of the present invention has high mechanical strength and low porosity. The detailed effects of the present invention will be described in conjunction with the following examples. DETAILED DESCRIPTION

[0021] The specific implementation methods of the present application are described in detail below, but it should be noted that the protection scope of the present application is not limited by these specific implementation methods, but is determined by the claims in the appendix.

[0022] Except for the embodiment section, any specific numerical value disclosed herein (including the endpoint of the numerical range) is not limited to the exact value of the numerical value, but should be understood to also cover values ​​close to the exact value, such as all possible numerical values ​​within the range of ±10% of the exact value. In addition, for the disclosed numerical range, between the endpoint values ​​of the range, between the endpoint value and the specific point value in the range, and between each specific point value can be arbitrarily combined to obtain one or more new numerical ranges, and these new numerical ranges should also be regarded as specifically disclosed herein.

[0023] Unless otherwise specified, the terms used herein have the same meanings as those generally understood by those skilled in the art. If a term is defined herein and its definition is different from the general understanding in the art, the definition herein shall prevail. For example, "alcohol" in this article is a mixture of ethanol and water, and does not specifically refer to ethanol.

[0024] The materials used in the present invention are all provided by Elkem Carbon (China) Co., Ltd.

[0025] Embodiment 1

[0026] A bio-based binder includes alcohol with a purity of 55% to 65%, plant asphalt, syrup and starch, and the mass ratio of the alcohol, plant asphalt, syrup and starch is (20 to 25): (150 to 170): (70 to 85): (90 to 110).

[0027] Alcohol with a purity of 55% to 65% specifically means that the volume percentage of ethanol in the alcohol is 55% to 65%.

[0028] Embodiment 2

[0029] The method for preparing the bio-based binder comprises the following steps:

[0030] Step 1: Add 55% to 65% purity alcohol, vegetable asphalt, syrup, and starch into a stirring container, and mix them in a mass ratio of (20 to 25): (150 to 170): (70 to 85): (90 to 110);

[0031] Step 2: Stir the alcohol and starch at a speed of 40-60 r / min for 2-3 min at an ambient temperature of 20-30 degrees Celsius;

[0032] Step 3: Continue to add syrup and stir at a speed of 80-100 r / min for 5-8 min at an ambient temperature of 40-50 degrees Celsius;

[0033] Step 4: Continue to add plant asphalt and stir at a speed of 40 to 70 r / min for 10 to 15 minutes at an ambient temperature of 50 to 55 degrees Celsius to obtain a bio-based binder.

[0034] Embodiment 3

[0035] The electrode paste based on bio-based binder includes 80-90 parts by mass of aggregate, 10-20 parts by mass of bio-based binder, and 0.7-1.2 parts by mass of attapulgite, wherein the bio-based binder includes alcohol, plant asphalt, syrup, and starch with a purity of 55% to 65%, and the mass ratio of alcohol, plant asphalt, syrup, and starch is (20-25): (150-170): (70-85): (90-110).

[0036] Alcohol with a purity of 55% to 65% specifically means that the volume percentage of ethanol in the alcohol is 55% to 65%.

[0037] Embodiment 4

[0038] The method for preparing the electrode paste based on the bio-based binder comprises the following steps:

[0039] Step 1: Add 55% to 65% purity alcohol, vegetable asphalt, syrup, and starch into a stirring container, and mix them in a mass ratio of (20 to 25): (150 to 170): (70 to 85): (90 to 110);

[0040] Step 2: Stir the alcohol and starch at a speed of 40-60 r / min for 2-3 min at an ambient temperature of 20-30 degrees Celsius;

[0041] At lower temperatures, starch is less viscous. When alcohol and starch are mixed, the starch surface will be covered by alcohol. Alcohol contains 35% to 45% water, which helps to disperse the starch. By stirring at a low speed, the alcohol will completely penetrate into the starch. After mixing, the starch will be loose and sandy. At the same time, at a lower temperature, alcohol is not easy to volatilize, which is conducive to the subsequent steps.

[0042] Step 3: Continue to add syrup and stir at a speed of 80-100 r / min for 5-8 min at an ambient temperature of 40-50 degrees Celsius;

[0043] Starch is a non-polar molecule, while sucrose and water in syrup are polar molecules. When the two are mixed together, they easily clump together and are difficult to mix evenly. In step 2, alcohol is coated on the surface of starch, and water and ethanol in alcohol are polar molecules, so starch is easier to disperse from syrup. At the same time, within the temperature range of 40 to 50 degrees Celsius, the viscosity of syrup is lower than that at room temperature. In this way, after 5 to 8 minutes of stirring, starch and syrup can be mixed evenly.

[0044] Step 4: Continue to add plant asphalt and stir at a speed of 40 to 70 r / min for 10 to 15 minutes at an ambient temperature of 50 to 55 degrees Celsius to obtain a bio-based binder;

[0045] The composition of plant asphalt is relatively complex, and its viscosity is relatively high and its fluidity is poor. At the same time, the viscosity of syrup is also relatively high. If plant asphalt is directly mixed into the mixture of starch and syrup, it is difficult to mix evenly. After the syrup is mixed with starch, the viscosity of the mixture decreases significantly due to the low viscosity of starch and the addition of low-viscosity alcohol. At higher temperatures, the viscosity of plant asphalt decreases. At the same time, at this temperature, the starch has not yet gelatinized and the viscosity is still relatively low. Therefore, plant asphalt can be well mixed with the mixture of starch and syrup. At the same time, as the stirring proceeds, most of the alcohol will gradually evaporate from the mixture, and a small amount of alcohol will remain in the bio-based binder. In addition, the physical properties of starch have not changed significantly, and the overall viscosity of the bio-based binder has not yet reached expectations.

[0046] Step 5: Mix the bio-based binder, aggregate and attapulgite and knead them into shape, wherein the mass ratio of the aggregate, the bio-based binder and the attapulgite is (80-90):(10-20):(0.7-1.2), the kneading temperature is 55-75 degrees Celsius, and the time is 50-60 minutes.

[0047] After that, after calcination according to the method specified in YS / T63.1-2019, electrode paste can be formed at room temperature.

[0048] In a preferred embodiment, the aggregate of the present invention is selected from one or more carbonaceous particles of electro-calcined anthracite, graphite, petroleum coke, asphalt coke and metallurgical coke.

[0049] In a preferred embodiment, among the aggregates, the mass ratio of aggregates with particle sizes of 4-12 mm, 2-4 mm, and 0-2 mm is 1:1:1.

[0050] In a preferred embodiment, in step 1, the stirring of alcohol, vegetable asphalt, syrup and starch is carried out in a closed stirring container to recover alcohol.

[0051] In a preferred embodiment, the starch is selected from one of corn starch, potato starch, tapioca starch, wheat starch and rice starch.

[0052] In the early stage of kneading, due to the presence of some alcohol and water, and the starch has not been completely gelatinized, the environmentally friendly binder and aggregate will be mixed more evenly. In the middle and late stages of kneading, with the volatilization of alcohol and the gelatinization of starch, the viscosity of the environmentally friendly binder increases, so that the aggregate can be better bonded. Specifically, the gelatinization of starch will first absorb the alcohol and the water in the syrup, which will increase the viscosity of the syrup, and the change in properties caused by the gelatinization of the starch itself will significantly increase its own viscosity, so that the aggregate is more tightly bound. The attapulgite is still in a dry state when it is added, which helps to mix the aggregate and the environmentally friendly binder. During the mixing process, the attapulgite absorbs water and the viscosity increases significantly, which is conducive to the close bonding of the aggregate.

[0053] The present invention has selected starch, syrup and plant asphalt as the main raw materials to prepare a binder suitable for electrode paste after exploration among many environmentally friendly materials with adhesive properties. Among them, the cost of starch as a binder is relatively low, so it can effectively reduce the production cost of electrode paste. However, due to the low viscosity of starch itself, including the low viscosity of starch after gelatinization, when the mixture is uneven, the mechanical strength of the electrode paste after subsequent baking is relatively low, and the electrode paste is prone to breakage. There are three difficulties in preparing starch, syrup and plant asphalt into a binder and kneading them with aggregate to form. The first is how to mix the binders of multiple components evenly, the second is how to mix the binder and aggregate evenly, and the third is whether the mechanical strength and porosity of the electrode paste after high-temperature baking can meet the requirements.

[0054] In view of the first difficulty, the present invention first adds alcohol to the raw materials of the binder, and then performs gradient mixing, and utilizes the characteristics of each component to achieve the purpose of uniformly mixing the components of the binder. Since alcohol is not needed in the electrode paste, and too much alcohol will lead to too much volatile matter in the electrode paste, which will affect the performance of the electrode paste, the present invention also utilizes temperature and time to volatilize most of the alcohol while uniformly mixing the binder in steps three and four, and the volatilized alcohol can be collected again.

[0055] In view of the second and third difficulties, the present invention utilizes the characteristics of low viscosity of starch when it is not gelatinized at low temperature, and the characteristics of low viscosity of attapulgite when it is dried, and fully mixes the binder with the aggregate. During the mixing process, the alcohol further evaporates, the starch gelatinization is denatured, and absorbs water, which not only increases its own viscosity, but also increases the viscosity of the syrup. At the same time, the viscosity of the attapulgite is also significantly increased after absorbing water, so that the compactness after kneading and molding is higher, and the mechanical strength and porosity are relatively low during subsequent roasting. The following invention will verify the effect of the present invention through Example 4 and Comparative Examples.

[0056] Embodiment 5

[0057] Alcohol with a purity of 55%, plant asphalt, syrup and starch are mixed in a mass ratio of 20:150:70:90, and then the alcohol and starch are stirred at a speed of 40r / min, a time of 2min, and an ambient temperature of 20 degrees Celsius; syrup is continued to be added for stirring at a speed of 80r / min, a time of 5min, and an ambient temperature of 40 degrees Celsius; plant asphalt is continued to be added for stirring at a speed of 40r / min, a time of 15min, and an ambient temperature of 50 degrees Celsius to obtain a bio-based binder; the bio-based binder, aggregate and attapulgite are mixed and kneaded to form, wherein the mass ratio of aggregate, bio-based binder and attapulgite is 80:20:0.7, the kneading temperature is 60 degrees Celsius, and the time is 60 minutes. After roasting according to the method specified in YS / T63.1-2019, the electrode paste is obtained at room temperature.

[0058] Comparative Example 1

[0059] The mass ratio of plant asphalt, syrup and starch was 150:70:90 and mixed for 22 minutes at a speed of 50r / min and an ambient temperature of 50 degrees Celsius to obtain a binder; the binder, aggregate and attapulgite were mixed and kneaded, wherein the mass ratio of aggregate, binder and attapulgite was 80:20:0.7, the kneading temperature was 60 degrees Celsius and the time was 60 minutes. After calcination according to the method specified in YS / T63.1-2019, the electrode paste was obtained at room temperature.

[0060] Comparative Example 2

[0061] The mass ratio of plant asphalt, syrup and starch was 150:70:90 and mixed for 22 minutes at a speed of 50r / min and an ambient temperature of 50 degrees Celsius to obtain a binder; the binder and aggregate were mixed and kneaded, wherein the mass ratio of aggregate to binder was 80:20:0.7, the kneading temperature was 60 degrees Celsius, and the time was 60 minutes. After calcination according to the method specified in YS / T63.1-2019, the electrode paste was obtained at room temperature.

[0062] Comparative Example 3

[0063] The plant asphalt, syrup, and gelatinized starch were mixed in a mass ratio of 150:70:90 for 22 minutes at a speed of 50r / min and an ambient temperature of 50 degrees Celsius to obtain a binder; the binder, aggregate, and attapulgite were mixed and kneaded, wherein the mass ratio of aggregate, binder, and attapulgite was 80:20:0.7, the kneading temperature was 60 degrees Celsius, and the time was 60 minutes. After calcination according to the method specified in YS / T63.1-2019, the electrode paste was obtained at room temperature.

[0064] Example 5 is an electrode paste prepared by the method of the present invention; Comparative Example 1 is an electrode paste prepared without adding alcohol and without following the bio-based binder step of the present invention; Comparative Example 2 is an electrode paste prepared without adding alcohol and without following the bio-based binder step of the present invention and without adding attapulgite; Comparative Example 3 is an electrode paste prepared without adding alcohol and replacing starch with gelatinized starch as the raw material and without following the bio-based binder step of the present invention. The experimental results are shown in Table 1:

[0065] Table 1: Properties of electrode pastes prepared in Example 5 and Comparative Examples 1, 2, and 3

[0066] Porosity (%) Mechanical strength (MPa) Embodiment 5 17.6 25.4 Comparative Example 1 20.9 19.1 Comparative Example 2 21.8 18.4 Comparative Example 3 22.3 17.5 standard 20% 22

[0067] Among them, the electrode paste performance in the standard column is the electrode paste performance that the industry needs to meet, that is,

[0068] Bulk density: non-ferrous metal industry standard YS / T 63.7;

[0069] Resistivity: Nonferrous metal industry standard YS / T 63.2;

[0070] Compressive strength: non-ferrous metal industry standard YS / T 63.15;

[0071] The above experimental results show that compared with comparative examples 1 to 3, embodiment 5 of the present invention has significant advantages in porosity and mechanical strength. Compared with the performance of standard electrode paste, the electrode paste performance of comparative examples 1, 2 and 3 does not meet the standard, and only the electrode paste of the present invention meets the standard.

[0072] What is disclosed above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. A person skilled in the art can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A bio-based binder, characterized in that: It includes alcohol with a purity of 55% to 65%, vegetable asphalt, syrup and starch, and the mass ratio of the alcohol, vegetable asphalt, syrup and starch is (20 to 25): (150 to 170): (70 to 85): (90 to 110).

2. A method for preparing a bio-based binder, characterized in that: The following steps are involved: Step 1: Add 55% to 65% purity alcohol, vegetable asphalt, syrup, and starch into a closed stirring container, and mix them in a mass ratio of (20 to 25): (150 to 170): (70 to 85): (90 to 110); Step 2: Stir the alcohol and starch at a speed of 40-60 r / min for 2-3 min at an ambient temperature of 20-30 degrees Celsius; Step 3: Continue to add syrup and stir at a speed of 80-100 r / min for 5-8 min at an ambient temperature of 40-50 degrees Celsius; Step 4: Continue to add plant asphalt and stir at a speed of 40 to 70 r / min for 10 to 15 minutes at an ambient temperature of 50 to 55 degrees Celsius to obtain a bio-based binder.

3. The method for preparing a bio-based binder according to claim 2, characterized in that: In step 1, the alcohol, vegetable asphalt, syrup and starch are stirred in a closed stirring container to recover the alcohol.

4. The method for preparing a bio-based binder according to claim 2 or 3, characterized in that: The starch is selected from one of corn starch, potato starch, tapioca starch, wheat starch and rice starch.

5. An electrode paste based on a bio-based binder, characterized in that: It includes 80 to 90 parts by mass of aggregate, 10 to 20 parts by mass of bio-based binder, and 0.7 to 1.2 parts by mass of attapulgite, wherein the bio-based binder includes alcohol, plant asphalt, syrup, and starch with a purity of 55% to 65%, and the mass ratio of alcohol, plant asphalt, syrup, and starch is (20 to 25): (150 to 170): (70 to 85): (90 to 110).

6. A method for preparing an electrode paste based on a bio-based binder comprises the following steps: Step 1: Add 55% to 65% purity alcohol, vegetable asphalt, syrup, and starch into a stirring container, and mix them in a mass ratio of (20 to 25): (150 to 170): (70 to 85): (90 to 110); Step 2: Stir the alcohol and starch at a speed of 40-60 r / min for 2-3 min at an ambient temperature of 20-30 degrees Celsius; Step 3: Continue to add syrup and stir at a speed of 80-100 r / min for 5-8 min at an ambient temperature of 40-50 degrees Celsius; Step 4: Continue to add plant asphalt and stir at a speed of 40 to 70 r / min for 10 to 15 minutes at an ambient temperature of 50 to 55 degrees Celsius to obtain a bio-based binder; Step 5: Mix the bio-based binder, aggregate and attapulgite and knead them into shape, wherein the mass ratio of the aggregate, the environmentally friendly binder and the attapulgite is (80-90):(10-20):(0.7-1.2), the kneading temperature is 55-75 degrees Celsius, and the time is 50-60 minutes.

7. The method for preparing an electrode paste based on a bio-based binder according to claim 6, characterized in that: The aggregate in step five is selected from one or more carbonaceous particles of electro-calcined anthracite, graphite, petroleum coke, asphalt coke and metallurgical coke.

8. The method for preparing an electrode paste based on a bio-based binder according to claim 6, characterized in that: In the aggregate of step five, the mass ratio of aggregates with particle sizes of 4-12 mm, 2-4 mm, and 0-2 mm is 1:1:

1.

9. The method for preparing an electrode paste based on a bio-based binder according to claim 6, characterized in that: In step 1, the alcohol, vegetable asphalt, syrup and starch are stirred in a closed stirring container to recover the alcohol.

10. The method for preparing an electrode paste based on a bio-based binder according to any one of claims 6 to 9, characterized in that: The starch is selected from one of corn starch, potato starch, tapioca starch, wheat starch and rice starch.

Citation Information

Patent Citations

  • Powerful cement and preparation method thereof

    CN102040924A

  • Environment-friendly carbon anode for aluminum electrolysis and preparation method thereof

    CN115874229A

  • Graphite electrode binder, preparation method of graphite electrode binder, graphite electrode and preparation method of graphite electrode

    CN116354725A

  • Composite biomass binder modified alkali-activated cementing material and preparation method thereof

    CN116947338A

  • Calcined coke, preparation method thereof and carbon anode

    CN117684218A

Cited By

  • Electrode paste and preparation method thereof

    CN121506581A